(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
In today’s era of globalization, the education system as an important component of society’s life needs to develop and improve, to serve the interests of a fundamentally renewed society, and to be competitive like the education system of developed countries. Enriching the critical thinking skills of future teachers today means equipping schoolchildren with the same skills.